2020
DOI: 10.2147/ott.s233244
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictive Value of Lymphocyte-Related Blood Parameters at the Time Point of Lymphocyte Nadir During Radiotherapy in Breast Cancer</p>

Abstract: Purpose: Various reports found a relationship between lymphocyte-related blood parameters (LRBP), including absolute lymphocyte counts (ALC), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) and prognosis of breast cancer. Most of the studies focused on LRBP pre-treatment. Seldom have studies focused on LRBP during radiotherapy. We intended to perform a retrospective cohort study on the prognostic value of LRBP at the time point of lowest ALC during radiotherapy for breast cancer. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…1938 The characteristics of the included studies are summarized in Table 1. The 20 studies 1938 were published between 2014 and 2021 with the sample size ranging from 62 to 1083; 12 studies were carried out in Asian countries and 8 studies in other regions. Pathological types included HER2 positive and negative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1938 The characteristics of the included studies are summarized in Table 1. The 20 studies 1938 were published between 2014 and 2021 with the sample size ranging from 62 to 1083; 12 studies were carried out in Asian countries and 8 studies in other regions. Pathological types included HER2 positive and negative.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis was adopted in 19 studies. 1938 The follow-up months ranged from 60 to 200 months in these studies, with NOS scores of 6–8 points (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on FBC have shown that patient-related inflammatory factors play a role in tumor initiation, formation, development, recurrence, metastasis, and treatment response. High NLR, PLR, and low LMR are reported as prognostic factors associated with survival 3,22,23 . In the study by Sun et al comparing HIP values of healthy and FBC patients, MPV, RDW, NLR, and PLR values were found higher in FBC patients 6 .…”
Section: Discussionmentioning
confidence: 99%
“…TNBC is an heterogenous and aggressive breast cancer defined by the absence of oestrogen receptor, progesterone receptor and HER2 47 . An elevated NLR is also associated with a poor response in patients submitted to radiotherapy or neo‐adjuvant chemotherapy treatments 48,49 . Even in patients with metastatic disease, the presence of lower NLR showed to be indicative of a better prognosis 50,51 …”
Section: Introductionmentioning
confidence: 99%